2021
DOI: 10.1128/msphere.00467-21
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Dietary Shifts Alter the Gut Microbiota of Avivorous Bats: Implication for Adaptation to Energy Harvest and Nutritional Utilization

Abstract: The coevolution between the host and its gut microbes can promote an animal’s adaptation to its specific ecological niche and changes in energy and nutritional requirements. This study focused on an avivorous bat, the great evening bat ( Ia io ), to investigate how seasonal dietary shifts affect the gut microbial composition and function, thereby facilitating adaptation to an avian diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
3
13
0
Order By: Relevance
“…The ratio of protein in food also showed an upward trend from SW to SK to PP ( Supplementary Table 1 ). Therefore, these results implied that the higher Firmicutes-to-Bacteroidetes ratio may help SK and PP to obtain more energy from a protein-rich diet ( De Filippo et al, 2010 ; Gong et al, 2021 ). Furthermore, the relative abundance of Cyanobacteria in gut microbes significantly decreased from SW to SK and PP ( Supplementary Table 2 ).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The ratio of protein in food also showed an upward trend from SW to SK to PP ( Supplementary Table 1 ). Therefore, these results implied that the higher Firmicutes-to-Bacteroidetes ratio may help SK and PP to obtain more energy from a protein-rich diet ( De Filippo et al, 2010 ; Gong et al, 2021 ). Furthermore, the relative abundance of Cyanobacteria in gut microbes significantly decreased from SW to SK and PP ( Supplementary Table 2 ).…”
Section: Discussionmentioning
confidence: 89%
“…Fish gut microbiota plays an important role in nutrition digestion and absorption ( Wu et al, 2015 ; Liu et al, 2016 ; Li et al, 2017 ). Previous studies have reported that host feeding on more protein may result in a greater Firmicutes-to-Bacteroidetes ratio of the gut microbiome ( De Filippo et al, 2010 ; Gong et al, 2021 ). At the phylum level, we found that the Firmicutes-to-Bacteroidetes ratio exhibited an upward trend from SW to SK and PP ( Supplementary Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypervariable region V3-V4 of the bacterial 16S rRNA gene was amplified with primer pairs 338F and 806R (Herlemann et al, 2011). PCR reactions were performed following the protocol described previously (Gong et al, 2021). The PCR product was extracted from 2% agarose gel and purified using the AxyPrep DNA Gel Extraction Kit (Axygen Biosciences, Union City, CA, USA) according to manufacturer's instruc- The raw sequences were merged by FLASH, version 1.2.7 (Magoc & Salzberg, 2011) and imported and processed with The Quantitative Insights into Microbial Ecology Version 2 (QIIME2) for further bioinformatics analysis (Bolyen et al, 2019).…”
Section: S Rrna Gene Sequencingmentioning
confidence: 99%
“…Several factors influence the colonization of microbial communities in the gut. Host phylogeny, growth stage, diet and health status have been shown to affect the composition and diversity of gut bacterial communities [3,4]. In addition, microorganisms in the external environment may contribute to the establishment of microbial communities in the guts of animals.…”
Section: Introductionmentioning
confidence: 99%